ELDERLY UKRAINIAN REFUGEES IN THE UK AND THEIR COMMUNICATION ADAPTATION - Babushko, Svitlana; Halytska, Maiia; Balchin, Kevin (European Science, 2025)
The paper investigates the communicative adaptation of elderly Ukrainian refugees in the UK following the 2022 invasion. It highlights communication as a crucial tool for integration, especially for vulnerable populations like the elderly, who face unique